ANALYSIS OF POLLUTION LOAD CAPACITY FROM FLOATING NET CAGE ON OPTIMAL MANAGEMENT STOCHASTIC DISCRETE MARKOV OF SAGULING RESERVOIR, WEST JAVA - Mushfiroh, Arini
The Saguling Reservoir is one of the Citarum cascade reservoirs located in the upstream area of West Java, which functions as a hydroelectric power plant (PLTA), a water supply provider for irrigation, and flood control. Utilization of reservoir waters for fisheries activities, especially aquaculture with Floating Net Cage (KJA) system, must be based on the carrying capacity of the waters, the amount of which depends on the fertility level of the reservoir. This research aims to examine the capacity of water pollution load from floating net cages to the operational management of Saguling Reservoir, West Java based on reservoir operation patterns. The research methodology used was analysis of water quality status and optimization of reservoir management carried out by Discrete Markov discharge classification. Calculation of the capacity of lake pollution load refers to Minister of Environment Regulation No. LH. 28 of 2009 based on the pattern of reservoir management in accordance with Government Regulation No. 37 of 2010 concerning Dams consisting of dry, normal, and wet years operating patterns. Analysis of water quality of Saguling Reservoir, based on STORET method is classified as medium polluted, while based on Pollution Index (PI) method is classified as heavy polluted, according to the criteria in the Decision of Minister of Environment Number 115 of 2003 on Guidelines for Determining Water Quality Status. This study showed that the Saguling Reservoir has the lowest pollution load capacity in the dry year with the value results in the dry, normal, and wet years respectively are 5.212,7x106 gram P per year, 6.003,7x106 gram P per year, dan 6.423x106 gram P per year.